Cancer-Related Bone Pain: Patients’ Satisfaction with Analgesic Pain Control - Andrew Tabu Kaggwa; Protus Werunga Kituyi; Elijah Nzeki Muteti; Ramadhani Barry Ayumba (The Annals of African Surgery, 2022)
Background: Management of cancer-related bone pain (CRBP) with analgesics poses a substantial challenge. This study aimed to determine the correlation between pain control satisfaction and prescribed analgesics. Methods: This 12-month descriptive prospective study included 96 adults who were consecutively sampled and followed up daily for 5 days. Eligible patients had histopathologically confirmed tumor, osseous lesion(s) on radiographs, and cognitive capacity to rank pain on the Numerical Rating Scale. Data were collected using questionnaires drafted from the Brief Pain Inventory. Self-assessed pain scores within the past 24 hours were reported on a scale of 0 (no pain) to 10 (worst pain). Pain control satisfaction was assessed as a single response question (satisfied, not sure, or dissatisfied). Associations were examined in multiple logistic regression models. Ethical approval and informed consent were obtained. Results: The median age was 57 (range, 19–90) years, and more males (52.1%) than females were recruited. The proportion of CRBP ranged from 83.3% to 86.5%, whereas that of moderate to severe pain ranged from 57.3% to 69.8%. Overall, 70.8% were satisfied with their pain control. Patients prescribed opioids (adjusted odds ratio, 0.027; p=0.041) had an increased likelihood of pain control satisfaction. Conclusion: Although a high percentage of patients experienced moderate to severe CRBP, a majority were satisfied with their analgesic pain control. Prescription opioids were associated with higher satisfaction. Policies that sustain ready accessibility of analgesics, particularly opioids, should be implemented.